Knowledge mapping of autistic traits: a visual analysis via CiteSpace - Qiao, Fu-Qiang; Du, Tong-Tong; Guo, Yingao; Dong, Ya-Jie; Li, Si-Ning; Qiang, Xu; Wang, Duan-Wei (Frontiers in Psychiatry, 2025)
ObjectiveThe aim of this study was to analyze the research hotspots and frontiers in the field of autistic traits (AT) between 1997 and 2024.MethodsThe Web of Science Core Collection (WOSCC) is used as a data source in the study, analyzing 1,044 academic articles on AT published between 1997 and 2024. The included articles were visually analyzed using CiteSpace 6.2.R4 software, which is used to map keywords and core literature related to AT and to analyze research progress and emerging hotspots in the fieldResultsA total of 1,044 articles have been included in the analysis, and the total number of articles has demonstrated an upward trajectory. The nations of England, the USA, and Australia are at the vanguard of this body of literature. With regard to research institutions, the University of London has attracted considerable attention as a result of its substantial contributions to the field of AT. The most relevant research is published in the Journal of Autism and Developmental Disorders.ConclusionThe scope of AT research has expanded considerably, encompassing psychology, education, and other disciplines. The research dimensions extend beyond behavioral, genetic, cognitive, and neural aspects to include environmental and hormonal factors. Furthermore, the study population has evolved from twins and the general population to focus on specific groups, such as individuals with psychiatric disorders. This broadening of focus has led to a significant increase in AT research in recent years. In sum, this study provides a comprehensive perspective that can inform and guide further in-depth research on AT.